2020
DOI: 10.3390/polym12040867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Current and Temperature on Extremely Low Loading Epoxy-CNT Conductive Composites

Abstract: Carbon nanotube (CNT) conductive composites have attracted significant attention for their potential use in applications such as electrostatic dissipation and/or electromagnetic interference shielding. The focus of this work is to evaluate resistivity trends of extremely low loading (<0.1 wt%) epoxy-CNT composites that lack a connected CNT network, but still present electrical conductivity values appropriate for those uses. The impact of current, temperature, and cycle life on electrical properties are here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…It was found that above 0.10% CNT loading, a continuous percolation network is formed, with the concurrent dramatic increase in conductivity [33]. Subsequent work showed that below 0.10% the mechanism of conduction is dominated by a capacitive-like behavior [36]. Similar findings were published by others providing a proof of concept that CNT conductive composites, even at very low CNT loadings, have potential for EMI applications [32,34,[37][38][39].…”
Section: Cnt Composites In Emi Uses and Microwave Absorption Studiessupporting
confidence: 65%
“…It was found that above 0.10% CNT loading, a continuous percolation network is formed, with the concurrent dramatic increase in conductivity [33]. Subsequent work showed that below 0.10% the mechanism of conduction is dominated by a capacitive-like behavior [36]. Similar findings were published by others providing a proof of concept that CNT conductive composites, even at very low CNT loadings, have potential for EMI applications [32,34,[37][38][39].…”
Section: Cnt Composites In Emi Uses and Microwave Absorption Studiessupporting
confidence: 65%
“…Figure 9(b) shows the variation of electrical resistance as function of temperature. It is known that the electrical resistivity of polymer nanocomposites is affected by temperature, 57 but the question is still unsolved since some authors have experienced a reduction of resistance increasing temperature, 58 while some others have found the opposite behavior. 59 In our case, all the formulations show an increase of electrical resistance increasing the temperature.…”
Section: Preliminary Characterizationsmentioning
confidence: 99%
“…This current dependence with increasing current application is ascribed to temperature increases due to resistive heating and irreversibility in the conductive path within the composite. Further discussion can be found in [ 1 ]. Notably, a reduction in resistivity (increased conductivity) is a positive attribute for the proposed applications.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoscale composites utilizing carbon nanotube (CNT) filler allow for significant reductions in resistivity of an otherwise highly insulating matrix material while requiring extremely low CNT loadings [ 1 ]. These improved conductivities result in an attractive material with extensive applications in diverse industries, but particularly for electrostatic discharge (ESD) and electromagnetic interference (EMI) prevention [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%